COMPLICATIONS OF TYPE 1 DIABETES MELITUS IN CHILDREN - Miolski, Jelena; Ješić, Maja; Zdravković, Vera (Medicinski podmladak, 2020)
The World Health Organization has defined Diabetes mellitus as a disorder of metabolism of various causes, due to lack of secretion and / or action of insulin, with long-term hyperglycemia and altered metabolism of sugars, proteins and fats. Diabetes mellitus is the most widespread chronic non-infectious disease, with an increase in the frequency in childhood that could be the epidemic of the 21st century.The incidence is rapidly increasing in the world, while in the last thirty years in Serbia there has been an increase in the number of patients especially in the group of small and preschool children. Exposure to the genetic, immune and environmental factors plays an important role in the etiology of the disease, but the underlying mechanisms remain unknown. Weeks before the final diagnosis, weakness, irresistible hunger, weight loss, increased thirst, pronounced diuresis, drying of the mucous membranes, skin pruritus, blurred vision could be present. Inadequate glycemic control and unregulated lipid status of children with type 1 diabetes are compatible with numerous complications and a higher risk of cardiovascular, peripheral vascular and cerebrovascular diseases. The therapy consists of insulin therapy, adequate daily physical activity, a variety of diets, overcoming stressful life situations and maintaining satisfactory metabolic control. By using intensive insulin therapy, the best control of the disease is achieved, while the frequency of possible complications is reduced.